2000
DOI: 10.1037/1061-4087.52.4.248
|View full text |Cite
|
Sign up to set email alerts
|

Can asking questions by computer improve the candidness of responding? A meta-analytic perspective.

Abstract: The effect of computerized testing on the candidness of self-reports was meta-analytically assessed. The authors proposed that respondents would reveal more embarrassing information when assessed by computer rather than when assessed in person or by paper-and-pencil measures. Results supported the hypothesis that asking questions about sensitive behaviors by computer produced more candid responding as compared with more traditional methods of assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…It appears to be a generally well accepted format with research demonstrating more candid responding via Internet (Feigelson & Dwight, 2000;Joinson, 1999), and it is certainly a more convenient and flexible mode of administration for both researchers/clinicians and respondents. It is critical to acknowledge, however, that Internet-based testing does not enable test administrators to informally or qualitatively evaluate behavioral aspects of test-taking behavior that may be relevant to the situation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…It appears to be a generally well accepted format with research demonstrating more candid responding via Internet (Feigelson & Dwight, 2000;Joinson, 1999), and it is certainly a more convenient and flexible mode of administration for both researchers/clinicians and respondents. It is critical to acknowledge, however, that Internet-based testing does not enable test administrators to informally or qualitatively evaluate behavioral aspects of test-taking behavior that may be relevant to the situation.…”
Section: Discussionmentioning
confidence: 93%
“…There is, in fact, evidence that Internet-based questionnaires are less susceptible to social desirability bias and yield more candid responses (Feigelson & Dwight, 2000;Joinson, 1999). In a meta-analytic study, Richman, Kiesler, Weisband, and Drasgow (1999) found that computerized questionnaires were prone to less social desirability bias if respondents could backtrack (and thus adjust answers prior to submitting), but conversely more bias if they could not do so (i.e., items were administered in a 26 AUSTIN, CARLBRING, RICHARDS, ANDERSSON "lock-step" fashion).…”
mentioning
confidence: 97%
“…41,42 Computer-based surveys have been shown to be acceptable to adults and to elicit more truthful responses on some sensitive health issues than in-person interviews. [43][44][45][46] Though providers may hesitate to use electronic surveys to elicit information on what could be sensitive topics, research in health care settings has shown greater disclosure by adolescents, adults, and adult caregivers via computer-based screenings versus face-to-face interviews on highly sensitive items surrounding substance use, sexual behavior, and intimate partner violence, [46][47][48][49][50][51][52][53][54][55][56][57] with some of this work done in ED settings. 50,58 In line with results from the current study, other studies have found little difference in reporting rates for less sensitive items across these formats.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, prior research has found that information collected via computer is valid compared to paper and pencil surveys. 2 Participants may be more candid with computers, 5 increasing the desirability of computer administration for sensitive topics such as alcohol use. Given this promise, it is critical to determine if patients are comfortable using computers during routine primary care encounters.…”
Section: Introductionmentioning
confidence: 99%